The Art News (voortzetting van : Hyde's Weekly Art News (1902); American Art News (1904-1923) ; The Art News (1923- ); titel varieert: Art News). (New York City : Artnews Associates, 1902)
Founded in 1902, ARTnews is the oldest and most widely circulated art magazine in the world. Its readership of 180,000 in 124 countries includes collectors, dealers, historians, artists, museum directors, curators, connoisseurs, and enthusiasts. Published in print six times a year, it reports on the art, people, issues, trends, and events shaping the international art world. The magazine’s thousands of contributors have included Alfred Barr, Bernard Berenson, Kenneth Clark, Robert Coles, Arthur Danto, Carlos Fuentes, Pete Hamill, Aldous Huxley, Steve Martin, Louise Nevelson, Bob Nickas, Francine Prose, Harold Rosenberg, David Salle, Jean-Paul Sartre, and William Carlos Williams.(www.artnews.com)
Https://www.artnews.com/about-us
Online: https://archive.org/details/pub_artnews
Engels
Tijdschriften